KINERJA KANTOR KECAMATAN DALAM PELAYANAN ADMINISTRASI DI POSO PESISIR UTARA KABUPATEN POSO - Lahada, Galib (Katalogis, 2015)
This research aims at finding out the performance of district office in administration service at Poso Pesisir Utara, Poso rgency.the method of this research is a qualitative with 11 informants selected by using purposive sampling. Techniques of the data collection of this research are: observation, interviews, and documentations. The result of this research shows that the performance of district Office at Poso Pesisir Utara Poso Regency has not met the expectation of the society. It can be seen from the level of understanding of the duties and functions in accordance with applicable regulations, the sensitivity of the job duties with the results achieved and priorities to task and urgent works and consistency between the tasks and the functions of each section with the activities carried out by the DistrictÂ  Office at Poso Pesisir Utara and acuntability to police donorÂ  while the level of tasks and works conformity with the result achieved and the conformity between policy and tasks implementation and work in general are in accordance with the provisions set. It can be seen that the level of productivity is quite high. To improve the pervormance it is needed to carry out and educational training and the apparatus should have high consciousness in understanding their tasks, functions and the area cirmutance which wstablish programs an policy direction.